2016
DOI: 10.1136/heartjnl-2015-308994
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year prognostic model for patients with suspected angina attending a chest pain clinic

Abstract: Background and objectiveDiagnostic models used in the management of suspected angina provide no explicit information about prognosis. We present a new prognostic model of 10-year coronary mortality in patients presenting for the first time with suspected angina to complement the Diamond-Forrester diagnostic model of disease probability.Methods and resultsA multicentre cohort of 8762 patients with suspected angina was followed up for a median of 10 years during which 233 coronary deaths were observed. Developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
(21 reference statements)
0
6
0
2
Order By: Relevance
“…Now, indirect observations suggest that the Genders updated disease estimates, recommended in the European Society of Cardiology guideline, may be similarly unreliable. Thus, a recent study found that patients with disease estimates as high as 60%–90% (mean 74%) had an annualised coronary mortality rate of only 0.7% 15. This apparent mismatch between predicted disease and observed mortality emphasises the likely unreliability of the disease estimates and the importance of considering prognostic indicators in patients with suspected angina so that those at greatest risk might be identified.…”
Section: How Reliable Are Estimates Of Disease Probability?mentioning
confidence: 99%
See 2 more Smart Citations
“…Now, indirect observations suggest that the Genders updated disease estimates, recommended in the European Society of Cardiology guideline, may be similarly unreliable. Thus, a recent study found that patients with disease estimates as high as 60%–90% (mean 74%) had an annualised coronary mortality rate of only 0.7% 15. This apparent mismatch between predicted disease and observed mortality emphasises the likely unreliability of the disease estimates and the importance of considering prognostic indicators in patients with suspected angina so that those at greatest risk might be identified.…”
Section: How Reliable Are Estimates Of Disease Probability?mentioning
confidence: 99%
“…This apparent mismatch between predicted disease and observed mortality emphasises the likely unreliability of the disease estimates and the importance of considering prognostic indicators in patients with suspected angina so that those at greatest risk might be identified. The Prognosis In Suspected Angina model based on simple clinical factors available at the initial cardiological assessment has been internally validated in a large chest pain clinic cohort and shows strong associations with coronary mortality (c-statistic 0.83) 15. A desktop calculator is available and promises to emerge as an important clinical tool if further validation studies are favourable.…”
Section: How Reliable Are Estimates Of Disease Probability?mentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Since CV event rates have been falling, a successful risk model must reflect contemporary risk. Risk models have been developed for patients with stable CAD, some derived for specific subpopulations such as patients with anginal symptoms, 5–7 patients with suspected angina attending a chest pain clinic, 8 survivors of acute coronary syndromes, 9 populations including less stable participants with recent myocardial infarction (MI), 10 and patients recruited to clinical trials. 9–11 Many of these models do not reflect current clinical practice or absolute CV risk.…”
Section: Introductionmentioning
confidence: 99%
“…Outros escores como o CAD consortium (7) e o Diamond Forrester (8) são utilizados para predizer doença arterial coronária obstrutiva no paciente com dor torácica. Sekhri et al (9) publicaram um modelo de prognóstico em 10 anos para pacientes com suspeita de angina que se apresenta com dor torácica.…”
Section: Introductionunclassified